1978
DOI: 10.1093/ajcn/31.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Zinc deficiency: a cause of abnormal dark adaptation in cirrhotics1–4

Abstract: Six stable alcoholic cirrhotics with serum zinc less than 70 microgram/100 ml had abnormal dark adaptation responses (mean dark adapted final threshold 3.2 +/- 0.6 versus 2.1 +/- 0.2 log lux in 21 age matched controls, P less than 0.01). Serum vitamin A ranged from 15 to 37 microgram/100 ml. Zinc sulfate (220 mg/day) was fed to three patients for 1 to 2 weeks and dark adapted final thresholds fell 0.9, 0.4, and 1.2 log lux without concurrent rises in serum vitamin A. Two patients were treated initially with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(52 citation statements)
references
References 21 publications
1
51
0
Order By: Relevance
“…The same observation was made in pregnant monkeys Golub et al, 1984) and pregnant rats (Duncan and Hurley, 1978;Peters et al, 1986). Morrison et al (1978) observed such a zinc ± vitamin A interaction also in nonpregnant humans. Palin et al (1979) reported that zinc supplementation improved vitamin A status of rats.…”
Section: Introductionsupporting
confidence: 72%
“…The same observation was made in pregnant monkeys Golub et al, 1984) and pregnant rats (Duncan and Hurley, 1978;Peters et al, 1986). Morrison et al (1978) observed such a zinc ± vitamin A interaction also in nonpregnant humans. Palin et al (1979) reported that zinc supplementation improved vitamin A status of rats.…”
Section: Introductionsupporting
confidence: 72%
“…Thus, in situations such as in alcoholic cirrhosis, where reduced plasma vitamin A is accompanied by a poor zinc status, vitamin A supplementation alone did not improve the abnormal dark adaptation suffered by the patients [10]. However, normalization was accomplished when vitamin A was supplemented with zinc, suggesting that these patients had an inability to mobilize vitamin A from the liver.…”
Section: Discussionmentioning
confidence: 94%
“…The retinol carrier proteins, such as RBP and transthyretin (TTR), have been found to be decreased in the plasma and liver, as well as in the kidney, of STZ-induced diabetic rats [9], suggesting an impaired mobilization of vitamin A from its hepatic storage to the circulation. Zinc is required for the synthesis of RBP [10,11] and has been shown to promote the transport of vitamin A from the liver [12,13]. Since zinc metabolism is known to be perturbed in the presence of diabetes [14][15][16][17], it is possible that supplementation with this trace element may enhance the hepatic synthesis of RBP and thereby reverse the decreased plasma retinol found in diabetes.…”
mentioning
confidence: 99%
“…in which the speed and magnitude of the gradual increasing electrical response to short flashes of light is measured in the dark. The electroretinogram is abnormal in alcoholic cirrhosis (Morrison et al 1978) when it correlates with leucocyte Zn levels (Keeling et al 1982). and in experimental Zn depletion in the cat (Jacobson er al.…”
Section: Zomentioning
confidence: 99%